Solve
ut = uxx 0<x<l, t>0
u(0, t)= u(l, t)= 0
u(x, 0)= x(l-x) , 0<=x<=l
Solution
Solution can be found in the form u(x,t) = X(x)*T(t)
X’’/X = T’/T => X’’/X = T’/T = -λ2
X’’+ λ2X = 0 => X = Asin(λ*x) + Bcos(λ*x) . Here A,B are arbitrary constants.
From boundary condition u(0, t) = 0 => B = 0
From boundary condition u(l, t) = 0 => sin(λ*x) = 0 => λ = π*n/l (n = 1,2, …)
So X = Asin(π*n *x/l)
Equation on T gives now T’ + λ2 T = 0 => T = exp(- λ2 t) = exp(- (π*n/l)2 t)
And un = An* exp(- (π*n/l)2 t)* sin(π*n *x/l)
"u(x,t)=\\displaystyle\\sum_{n=1}^\\infty A_n e^{-(\\pi n\/l)^2t} sin(\\pi n \\frac{x}{l})"
From initial condition u(x, 0)= x(l-x) , 0<=x<=l
"x(l-x)=\\displaystyle\\sum_{n=1}^\\infty A_n sin(\\pi n \\frac{x}{l})"
"A_n=\\frac{\\displaystyle\\int_0^l x(l-x) sin(\\pi n x\/l) dx}{\\displaystyle\\int_0^l sin^2(\\pi n x\/l) dx}"
"A_n=\n\\frac{2}{l} \\displaystyle\\int_0^l x(l-x) sin(\\pi n x\/l) dx"
Let y = x/l => "A_n=\n2l^2 \\displaystyle\\int_0^1 y(1-y) sin(\\pi n y) dy"
Let z = π*n *y => "A_n=\n\\frac{2l^2}{(\\pi n)^2} \\displaystyle\\int_0^{\\pi n} z(1-\\frac{z}{\\pi n}) sin(z) dz"
"A_n=\\frac{2l^2}{(\\pi n)^2} [sin(z)-z cos(z)\n-\\frac{1}{\\pi n} (2z sin(z)-(z^2-2) cos(z))] |_0^{\\pi n}"
"A_n\u200b=\\frac{2l^2}{(\\pi n)^2} [\\pi n (-)^{n+1}+\\frac{1}{\\pi n}((\\pi n)^2-2)(-)^n+\\frac{2}{\\pi n}]"
"A_n\u200b=\\frac{4l^2}{(\\pi n)^3} [(-)^{n+1}+1]"
A2m = 0, A2m+1 = 8l2/(π*(2m+1))3 (m = 0,1, …)
"u(x,t)=8l^2\\displaystyle\\sum_{m=0}^\\infty \\frac{1}{(\\pi (2m+1))^3} e^{-(\\pi (2m+1)\/l)^2t} sin(\\pi (2m+1) \\frac{x}{l})"
Answer
"u(x,t)=8l^2\\displaystyle\\sum_{m=0}^\\infty \\frac{1}{(\\pi (2m+1))^3} e^{-(\\pi (2m+1)\/l)^2t} sin(\\pi (2m+1) \\frac{x}{l})"
Comments
Leave a comment